Empowering Women In Local Communities Through PT Borneo Indobara’s CSR Initiatives: Sustainable Strategies For Local Uniform Production - Aditia, Silvyna; Wisesa , Anggara (Pelopor Publikasi Akademika, 2025)
This study explores the role of Corporate Social Responsibility (CSR) in empowering women in local communities through PT Borneo Indobara’s initiatives, focusing on the sustainable production of uniforms. The research identifies key challenges faced by local tailors, including limited skills, outdated equipment, access to quality raw materials, and market constraints. By applying the Shared Value Framework (SVF) and Theory of Change (ToC), the study proposes solutions that integrate community empowerment with business strategies. Key recommendations include skills development for women, provision of modern sewing machines, and the creation of local supply chains for raw materials. The findings demonstrate that empowering local women through targeted training and financial support can significantly enhance their ability to meet industry standards, thereby fostering economic growth and improving local production capacity. The study also emphasizes the importance of collaboration between businesses, government, and local stakeholders in creating a sustainable model for local uniform production. This approach not only helps PT Borneo Indobara meet its uniform supply needs but also contributes to the broader social development of the community. The research provides a model that can be replicated by other industries looking to integrate CSR and CSV initiatives into their business operations, contributing to long-term sustainable development goals such as gender equality and inclusive economic growth.